Evolution of the cognitive profile in school-aged patients with severe TBI during the first 2 years of neurorehabilitation. (November 2013) - Bardoni, Alessandra; Galbiati, Susanna; Recla, Monica; Pastore, Valentina; Formica, Francesca; Strazzer, Sandra
Abstract Objective: Persistent post-injury cognitive, academic and behavioural deficits have been documented in children who sustained severe TBI during the school-age years. The major aim of this study was to examine and follow-up for 2 years the cognitive profile of a sample of post-injured patients (aged 6–16.11), in order to verify to what extent they recovered their intellectual functions after rehabilitation. Method: Twenty-six patients who received a specific neuropsychological treatment and three cognitive evaluations with WISC-III were selected from a pool of 77. Results: This group of patients showed a mild cognitive deficit at baseline, which improved over the 2 years to a borderline level. Despite the improvement in intellectual quotients and single sub-test scores achieved through rehabilitation, different recovery times were seen according to the function under study. The most common deficits are in processing speed, inferential and lexical-semantic skills. Conclusions: Detailed analysis of the WISC-III sub-tests allows for an accurate description of single cognitive functions after TBI. This allows one to make differential diagnoses between functional profiles and plan individualized rehabilitation treatments. Post-injured school-aged patients should receive rehabilitation for a period of at least 2 years, which is the time necessary for an at-least partial reorganization of basic cognitive functions.